PENGARUH PEMBERIAN KREDIT TERHADAP KEBERHASILAN USAHA ANGGOTA KOPERASI SIMPAN PINJAM SEPAKAT MAKMUR PEMANGKAT - Hajipah, Hajipah; Asriati, Nuraini; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This thesis entitled the influence or credit to the success of members of cooperatives savings and loan Sepakat Makmur Pemangkat, with the problem of research whether theÂ provision of credit affects the success of members of cooperatives savings and loan Sepakat Makmur Pemangkat. The method used is quantitative descriptive with the form of research relationship study. Population of 250 members apply for credit and with samples according to slovin formula amounting to 71 data members are taken with indirect communication techniques with questionnaires as well as documentation, while the data processing techniques using simple regression. The results of this study indicate that, 1) Credit provision savings and loan cooperatives Sepakat Makmur Pemangkat high category, 2) the success of memberâ€™s business is high, 3) The provision of credit affects the success of members cooperatives savings and loan , 4) The magnitude of influence is indicated by the formula Y= 16,198+0,586, which means the value of constant (a) of 16,198 can be interpreted if the credit giving value 0 then the success of the business is worth 16,198. The coefficient of determination from the results of this study shows the contribution of variable x to the success of member business of 47.1%.Keywords: Lending, Business success, and Savings Credit Cooperatives